Encyclopedia of Life Sciences 2009
DOI: 10.1002/9780470015902.a0021232
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem Boundaries

Abstract: Ecosystem boundaries are zones of transitions between two adjacent habitats. They occur naturally in all biomes but the extent of boundaries has been greatly increased by anthropogenic habitat modification. Transition zones are characterized by a profound change in the composition of plant and animal communities and that transition may be abrupt, gradual or even occur via a series of intermediate habitat types. Naturally occurring ecosystem boundaries sometimes form a unique habitat to which species are specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
0
7
0
2
Order By: Relevance
“…energy and nutrient flows) change abruptly in relation to those within a patch (Wiens et al ). Because boundaries differ in their permeability to material flows, the movement of materials occur over various temporal and spatial scales, which may dramatically alter material composition (Wiens et al , Banks‐Leite and Ewers ). Therefore, the movement of material may directly influence its stoichiometry, as nutrients are transformed in transit or used and discarded while crossing boundaries (Schade et al ).…”
Section: Impacts Of Spatial and Temporal Scales On The Stoichiometry mentioning
confidence: 99%
“…energy and nutrient flows) change abruptly in relation to those within a patch (Wiens et al ). Because boundaries differ in their permeability to material flows, the movement of materials occur over various temporal and spatial scales, which may dramatically alter material composition (Wiens et al , Banks‐Leite and Ewers ). Therefore, the movement of material may directly influence its stoichiometry, as nutrients are transformed in transit or used and discarded while crossing boundaries (Schade et al ).…”
Section: Impacts Of Spatial and Temporal Scales On The Stoichiometry mentioning
confidence: 99%
“…Third, the boundaries of a natural ecosystem are hard to define because adjacent ecosystems are often connected through flows of energy, materials, and organisms (Banks-Leite & Ewers, 2009). The same applies to conceptualizations of SUPIEs, where the flow of financial, human, and other resources can easily cross the boundaries of an individual ecosystem.…”
Section: Conceptualizing Supies: How Does the Environment Help Birds mentioning
confidence: 99%
“…Through the factor analysis of cell-based ecosystem service maps showing different indicators, two main types of ecosystems, mountains and flatlands, were extracted. Synergetic (e.g., underground water and carbon; farms, CO2, and erosion) and trade-off (e.g., rice paddies vs. underground water and carbon; scenic quality vs. farms, CO2, and erosion) relationships between the two ecosystem service types (mountains and agriculture) and their boundaries were identified, providing one method of finding the main ecosystems and boundaries that are often discussed theoretically (Banks-Leite & Ewers, 2009;Prieto-Torres & Rojas-Soto, 2016;Saunders & Briggs, 2002); beyond administrative districts (Haines-Young, Potschin, & Kienast, 2012;Hamann, Biggs, & Reyers, 2015;Jopke et al, 2015;Oakley et al, 2018;Queiroz et al, 2015;Raudsepp-Hearne, C, Peterson, & Bennett, 2010;Schulp et al, 2014). These results are consistent with previous studies that have grouped items and shown ecosystem service synergies and trade-offs, and examined how the corresponding areas were distributed in space (Früh-Müller et al, 2016;Qiu & Turner, 2013).…”
Section: Factor Analysismentioning
confidence: 99%